THE MEDIATING ROLE OF NON-PERFORMING LOANS ON THE RELATIONSHIP BETWEEN INCOME DIVERSIFICATION AND BANK PERFORMANCE EVIDENCE FROM INDONESIA - Shirley Wijaya; Kristi Indriyani (Politeknik Negeri Ambon, 2025)
Introduction: Income diversification and profitability are widely seen as strategies to reduce credit risk in banking. However, their effectiveness in improving asset quality remains debated, especially in emerging markets like Indonesia. This study focuses on how income diversification influences bank performance, with non-performing loans (NPLs) acting as a mediating variable Methods: Using quantitative method with panel data from 79 Indonesian banks listed on the OJK between 2018 and 2024. Data were obtained from audited financial reports and analyzed using fixed effect panel regression and mediation testing via the Sobel test. Income diversification is measured by the ratio of non-interest income to total income, NPLs by the NPL ratio, and bank performance by return on assets (ROA) Results: Income diversification reduces credit risk (NPLs) by expanding income sources beyond traditional lending. Despite reducing NPLs, income diversification introduces operational complexities and inefficiencies that can diminish bank performance. NPLs partially mediate the relationship between income diversification and bank performance, showing that improved credit quality alone is insufficient to enhance profitability without addressing internal management and operational challenges. Keywords: Bank Performance, Credit Risk, Income Diversification, Non-Performing Loans, Trade-off Theory